2017
DOI: 10.5817/sp2017-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Approaching trust and control in parental relationships with educational institutions

Abstract: Trust is a crucial factor in parent-teacher relationships. However, research on this subject to date has largely concentrated on a narrow range of theoretical perspectives and empirical methods. Most studies collect, analyze, and aggregate quantitative data on trust from a psychological or sociological perspective. The present paper starts by reflecting on previous research in brief and discussing its limitations with regard to a selected case: parents' relationships with educational institutions. On this basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Trust is a complex issue, as documented by philosophical, psychological, as well as sociological studies on the issue which adopt various theoretical perspectives. A useful starting point for our study is offered in the special issue of Studia paedagogica focusing on trust (and control) in education, especially in the text by Schweizer et al (2017), where trust is conceived as a holistic phenomenon that encompasses explicit as well as implicit dimensions. Trust stands as a base in human interactions of all kinds, i.e., trust in individuals, organisations and complex systems.…”
Section: The Professional Project In Teachingmentioning
confidence: 99%
“…Trust is a complex issue, as documented by philosophical, psychological, as well as sociological studies on the issue which adopt various theoretical perspectives. A useful starting point for our study is offered in the special issue of Studia paedagogica focusing on trust (and control) in education, especially in the text by Schweizer et al (2017), where trust is conceived as a holistic phenomenon that encompasses explicit as well as implicit dimensions. Trust stands as a base in human interactions of all kinds, i.e., trust in individuals, organisations and complex systems.…”
Section: The Professional Project In Teachingmentioning
confidence: 99%
“…Second, we were unable to collect demographic information on parents due to the privacy law as placed by FERPA, and inferred parental demographic information based on available student data. For example, parental race and ethnicity (Froiland & Davison, 2014), highest achieved education (Schweizer, Niedlich, Adamczyk, & Bormann, 2017), and family structure (Froiland & Davison, 2014) have been demonstrated to play a role in the level of parental trust and satisfaction with teacher interactions. Future studies should then explicitly collect demographic information on parents enrolled in the study.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…For example, Yulianti et al (2018) found that Indonesian parents showed a higher level of communication with school when mothers have a higher education level. Another study by Schweizer et al (2017) revealed that parents with higher educational backgrounds show greater eagerness to personally ensure their children's academic success. Conversely, parents with lower education levels trust teachers more.…”
Section: Introductionmentioning
confidence: 99%